Sosialisasi Ragam Program Studi dalam Rumpun Ilmu Komputer untuk Siswa SMA/SMK di Sumatera Barat - Dwi Welly Sukma Nirad; Ricky Akbar; Hifzhon Alnutari (Universitas Mathla'ul Anwar Banten, 2021)
SOCIALIZATION OF VARIOUS STUDY PROGRAMS IN COMPUTER SCIENCE CLUMS FOR SMA/SMK STUDENTS IN WEST SUMATERA. The international computer curriculum has determined that computer science has 5 courses of study. However, not all people know in detail about the scope of learning and competencies of each of these study programs. Ignorance of prospective students about this difference in scope can cause problems in the studies they take later, such as being not enthusiastic about studying because they feel that they are in the wrong major or students' unpreparedness in accepting the competence of the study program. Therefore, socialization is given to high school students in the hope of disseminating information and basic knowledge about the scope of the study of the various study programs so that it becomes a provision for the younger generation to choose an education that will determine their future careers. This socialization activity was attended by 36 participants from various schools in several different provinces. The results of the survey conducted at the end of the activity showed that 60.5% of the participants were confident about their choice of study plan. This percentage confirms that the objectives of the outreach activities have been well achieved.